Răspuns :
la primul:
4,5*1 intreg si 3/9+1=
4,5*12/9+ 1=
52,5/9+1/9=53,5/9=5,9(4)
al doilea e gresit...cred
4,5*1 intreg si 3/9+1=
4,5*12/9+ 1=
52,5/9+1/9=53,5/9=5,9(4)
al doilea e gresit...cred
[tex]a) 4,5*1,(3)+1=
[/tex]
[tex]=4 \frac{5}{10}+1 \frac{3}{9} =[/tex]
[tex]=4 \frac{1}{2} +1 \frac{1}{3}= [/tex]
[tex]= \frac{9}{2}+ \frac{4}{3}=[/tex]
[tex]= \frac{27}{6}+ \frac{8}{6}= [/tex]
[tex]= \frac{35}{6} [/tex]
[tex]b) (\frac{2}{5})^{12}: (\frac{4}{10})^2+4 \frac{84}{100} =[/tex]
[tex]=( \frac{2}{5})^{12}: (\frac{2}{5})^2+4 \frac{21}{25} = [/tex]
[tex]= (\frac{2}{5})^{12}* \frac{25}{4}+ \frac{121}{25}= [/tex]
[tex]= (\frac{2}{5})^{10}= \frac{2^{10}}{5^{10}} [/tex]
[tex]=4 \frac{5}{10}+1 \frac{3}{9} =[/tex]
[tex]=4 \frac{1}{2} +1 \frac{1}{3}= [/tex]
[tex]= \frac{9}{2}+ \frac{4}{3}=[/tex]
[tex]= \frac{27}{6}+ \frac{8}{6}= [/tex]
[tex]= \frac{35}{6} [/tex]
[tex]b) (\frac{2}{5})^{12}: (\frac{4}{10})^2+4 \frac{84}{100} =[/tex]
[tex]=( \frac{2}{5})^{12}: (\frac{2}{5})^2+4 \frac{21}{25} = [/tex]
[tex]= (\frac{2}{5})^{12}* \frac{25}{4}+ \frac{121}{25}= [/tex]
[tex]= (\frac{2}{5})^{10}= \frac{2^{10}}{5^{10}} [/tex]